الإشكال في الحديث وانواعه وضوابط حلوله : دراسة تطبيقية في كتاب مشكل الآثار للإمام الطحاوي - محمد، سامية زكريا (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The aim of this study is to explore the various types of problematic or equivocal Hadith and the standards of their interpretation, through the analysis of the book, Mushkil al-Athar [Equivocal Hadith] by Al-Imam al-tahawi (may Allah bless him). The researcher adopted two methods in this study, the inductive and the analytical methods to find out the types of equivocal Hadiths, and to examine the standards for solving the problem by applying these standards on examples in the book of Mushkil al-Athar. Through the study of the book the researcher found that there are different types of equivocal Hadith. Some of them seem to be contradicting with the Holy Quran, or other Hadith, or the consensus of the Ummah, as well as with analogical deduction (Qiyas) or the practices of Companions. There are some Hadith that seem to have impossible meanings, or have the concealed of their intended meanings. Other Hadith have controversial meanings among different narrators of Hadith, or scholars of Shariah, or reciters of the Quran, or linguists. There are also some Hadith that seem to be contradicting with historical facts or scientific realities. The researcher found that there are standards to solve all types of equivocality in Hadith. These standards comprise of some rules and principles used by Al-Imam al-tahawi (may Allah bless him) in his book to interpret all types of equivocal Hadith. Among these are combining the Hadith with the Quran or other Hadith giving preference to one over the other finding out abrogation of some Hadith and sometimes, holding of the interpretation and explaining the Hadith where the intended meaning is concealed or have impossible meanings.